Knowledge, Attitude and Practice (KAP) Towards Hepatitis B Vaccination Among HIV Patients at Nigeria Institute of Medical Research (NIMR), Yaba – Lagos: A Cross-Sectional Study - Ladan, Musa Sanni; Lateef, Akeem Blessing; Hamzat, Omolara Arafat (FUDMA Journal of Sciences, 2026)
The rate of Hepatitis B Virus (HBV) infection among HIV patients is higher than that of the general population. In spite of this challenge, there has been a low vaccination record among HIV patients.  The objective of this study is to assess the knowledge, attitude and practice of HIV patients towards Hepatitis B. An institutional–based cross-sectional study design was conducted among 309 HIV patients from September to November 2024. A pretested self-administered questionnaire was used to collect data regarding knowledge, attitude and practice towards hepatitis B vaccination.  Non-probability convenience sampling was also used.  Descriptive statistics were done by calculating frequencies and percentages of categorical independent variables and categorical dependent variables, using SPSS version 20. Among 309 HIV patients, 59.3% of them had good knowledge about the Hepatitis B virus and vaccination, with an average mean score of 4.21, and 51.6% had, a good attitude, with an average mean score of 4.31.  The practice was low, with only 37.4% receiving the complete dose of HB vaccine, with an average mean score of 31. There were a significant association of socio-demographic variables with knowledge, attitude and practice towards Hepatitis B vaccination. Although, the knowledge and attitude towards Hepatitis B vaccination are high, the practice levels are very low.  This indicates the need for immunising HIV positive patients against Hepatitis B and focusing more on preventive practices against HBV.
Keywords: Knowledge; Attitude; Practice; Hepatitis B; Vaccination; HIV Patients